Eksistensi Varietas Padi Lokal pada Berbagai Ekosistem Sawah Irigasi: Studi di Daerah Istimewa Yogyakarta - Samidjo, Gatot Supangkat (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2017)
A research was carried out to study the existence of rice local variety in the irrigated paddy fields in different ecosystems. The research was conducted from January 2013 to February 2014 in the Special Region of Yogyakarta. Observation and interview were used in this research for collecting the data. The largest irrigated rice fields were selected using stratified random sampling. Farmers as a respondent were selected by purposive sampling, based on rice variety grown on their paddy fields with the area of at least 1000 m2. Variables were observed in this research including rice variety distribution, farmer experience on planting local variety, physical ecological impacts, rice yield and economical yield component. Data was analyzed by spatial analysis and descriptive analysis. The result showed that rice local variety still existed in the fields, which Menthik and Menthik Susu were dominant local variety distributed in irrigated paddy fields ecosystem. The existence of local variety was indicated by the high percentage of the farmer experience in planting rice local variety. The highest yield and B/C (Benefit/Cost ratio) ratio were gained by Menthik variety compared with other local varieties.